Analysis of the Responsiveness of Non-Oil Exports to Fiscal and Monetary Policy Actions - Edeme, Richardson Kojo; Obiayo, Clifford Nworah (Journal of Accounting, Business and Finance Research, 2017)
The paper aims to examine the responsiveness of non-oil exports to monetary and fiscal policy actions and to ascertain if there is any significant difference in the response of non-oil exports to fiscal and monetary policy actions. Adopting the partial determination model, the paper found that there ismonetary-fiscal policy interaction effect in the short-run but the effect became undefined in the long-run. It was also revealed that the response of non-oil exports is dominated by fiscal policy actions than the responses to monetary policy. Also monetary policy influences are temporary whereas the fiscal policy effect seems permanent. In this regard, it will be more appropriate to place greater reliance on fiscal policy form of stabilization action. The adoption of mixed monetary-fiscal policy is also recommended. This is because, mixed monetary-fiscal policy actions operates more quickly and expand non-oil exports within a short while. Though, the interaction effect is undefined in the long run, it is appropriate to stimulate non-oil export in the short-run.